Acute Inhalation of Combustion Smoke Triggers Neuroinflammation and Persistent Anxiety-Like Behavior in the Mouse - Gorgun, Murat F. (Inhal Toxicol, 2018)
CONTEXT: Acute inhalation of combustion smoke triggers neurologic sequelae in survivors. Due to challenges posed by heterogeneity of smoke exposures in humans, mechanistic links between acute smoke inhalation and neuropathologic sequelae have not been systematically investigated. METHODS: Here, using mouse model of acute inhalation of combustion smoke, we studied longitudinal neurobehavioral manifestations of smoke exposures and molecular/cellular changes in the mouse brain. RESULTS: Immunohistochemical analyses at eight months post smoke, revealed hippocampal astrogliosis and microgliosis accompanied by reduced myelination. Elevated expression of proinflammatory cytokines was also detected. Longitudinal testing in different neurobehavioral paradigms in the course of post smoke recovery, revealed lasting anxiety-like behavior. The examined paradigms included the open field exploration/anxiety testing at two, four and six months post smoke, which detected decreases in total distance traveled and time spent in the central arena in the smoke exposed compared to sham control mice, suggestive of dampened exploratory activity and increased anxiety-like behavior. In agreement with reduced open field activity, cued fear conditioning test revealed increased freezing in response to conditioned auditory stimulus in mice after acute smoke inhalation. Similarly, elevated plus maze testing demonstrated lesser presence in open arms of the maze, consistent with anxiety-like behavior, for the post-smoke exposure mice. CONCLUSIONS: Taken together, our data demonstrate for the first time persistent neurobehavioral manifestations of acute inhalation of combustion smoke and provide new insights into long-term progression of events initiated by disrupted brain oxygenation that might contribute to lasting adverse sequelae in survivors of smoke inhalation injuries.